Identification of regularities of changes in energy-power parameters depending on the design of the roller node of a new radial-shear mill by computer simulation - Mashekov, Serik; Nurtazayev, Adilzhan Eleuovich; Mashekova, Aigerim; Nugman, Yerik; Angarbekov, Ulan (Eastern-European Journal of Enterprise Technologies, 2020)
This paper proposes a radial-shear mill (RSM) of a new design, which allows by rolling or rolling and pressing operations obtaining high-quality rods and wires. In addition, it proposes the method of computer calculation of the energy-power parameters of bar extrusion at the RSM of the new design. Mathematical dependences and calculation algorithm were described, which allow calculating energy-power parameters of the combined bar manufacturing process at a given level of technological parameters. Based on the results of analytical studies and computer modeling, the energy-power parameters were defined and analyzed, in addition, the laws of their changes were determined. It is shown that, regardless of the alloy grade or type, when rolling billets on a new RSM with smooth rolls, the strain force is larger in magnitude compared to rolling in helical rolls. It was found that, in comparison with rolling of bars in smooth and helical rolls, their processing by a combined rolling-pressing process leads to an increase in the deformation force of alloys M1 and D16 by 1.1–1.15 and 1.15–1.3 times, respectively. It is shown that during the deformation of the rods on the new RSM, by controlling the paths of the metal flow in the deformation zone, intensive grinding of the metal structure can be achieved. It was found that when pressing the bars on the new RSM, the temperature of the workpiece increases up to 420 °С, which leads to a sharp decrease in the force required for deformation. The nature of the temperature distribution of the pressed metal in the deformation zone was determined. The adequacy of the models was proved by comparing calculated values of the power parameters of extrusion, obtained by engineering technique and numerical simulation